Step-by-step explanation:
To solve this problem, let's denote the radius of the circle with center O as \( r \) and the radius of the circle with center N as \( R \). Since the radius of the circle with center O is twice that of the circle with center N, we have:
\[ r = 2R \]
Now, since OX is tangent to the circle with center N, we can use the property that a radius drawn to the point of tangency is perpendicular to the tangent. Thus, the triangle OXP is a right triangle, with OP being the hypotenuse, PX being the given tangent length, and OX being the unknown side.
We can use the Pythagorean theorem to find the length of OP:
\[ OP^2 = OX^2 + PX^2 \]
\[ OP^2 = 18^2 + (2R)^2 \]
\[ OP^2 = 324 + 4R^2 \]
Now, since OP = ON - NP and ON = 3R (since the radius of the circle with center O is twice that of the circle with center N), we have:
\[ OP = 3R - R = 2R \]
So, we can rewrite \( OP \) as \( 2R \), and we get:
\[ (2R)^2 = 324 + 4R^2 \]
\[ 4R^2 = 324 + 4R^2 \]
\[ 0 = 324 \]
This is not possible. Therefore, there seems to be a mistake in the problem statement or in the drawing provided. Can you please review the problem statement or provide any additional information or clarification?